PENGARUH MOTIVASI KERJA, IKLIM ORGANISASI DAN PENDIDIKAN PELATIHAN TERHADAP KINERJA GURU (Survei pada Guru SMA Negeri 1 Slogohimo, di Wonogiri) - Siti Wulandari; Alwi Suddin; Sutarno Sutarno (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the significance of the effect of work motivation, organizational climate and training education on teacher performance, in addition to finding out among the dominant variables of work motivation, organizational climate, and training education on the performance of teachers at Slogohimo 1 High School, Wonogiri. The type of data used is qualitative data and quantitative data. The data sources used are primary data and secondary data. The entire population in this study were all teachers of Slogohimo 1 High School, namely 48 people with census techniques. Data collection techniques in this study used questionnaires and documentation. The data analysis technique used, Descriptive Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test (Model Accuracy), and Determination Coefficient Test (R2 ). The results of this study indicate that work motivation has a significant effect on the performance of teachers at Slogohimo 1 Public High School, Wonogiri. The organizational climate did not significantly influence the performance of teachers at Slogohimo 1 Public High School, Wonogiri. Training education has a significant effect on the performance of teachers at Slogohimo 1 Public High School, Wonogiri. The result of the coefficient of determination (R2 ) is 0.517, this means that the contribution or influence given by the variables of work motivation, organizational climate and training education on teacher performance is 51.7% while the remaining 48.3% is influenced by other variables outside the variable examined, for example organizational culture, compensation, leadership, and others. Work motivation is the dominant variable that influences the performance of teachers at Slogohimo 1 Public High School, Wonogiri.